2018
DOI: 10.1515/cclm-2017-0430
|View full text |Cite
|
Sign up to set email alerts
|

High microRNA-28-5p expression in colorectal adenocarcinoma predicts short-term relapse of node-negative patients and poor overall survival of patients with non-metastatic disease

Abstract: High miR-28-5p expression predicts poor DFS and OS of colorectal adenocarcinoma patients, independently of clinicopathological prognosticators and standard patient treatment, including radiotherapy and chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
3
19
1
Order By: Relevance
“…The prognostic and predictive value improves by the synergy of more than two miRNAs, encouraging the development of multipurpose miRNA signatures as diagnostic or prognostic tools (46)(47)(48). For instance, combination of miR-15a-5p, miR-16, miR-24-3p, miR-28-5p, miR-34a, miR-96, miR-182, and miR-224, which have been proposed as molecular biomarkers with significant prognostic value in colorectal cancer (CRC); has already been proposed as a prognostic signature in this malignancy (49)(50)(51)(52)(53)(54)(55)(56)(57); another very important miRNA that could be added in this molecular signature is miR-21, a predictor of metastatic tumor potential in this cancer (58). Similar signatures consisting of miRNAs have been proposed in prostate cancer (59,60), laryngeal squamous cell carcinoma (61), and other human malignancies (62).…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic and predictive value improves by the synergy of more than two miRNAs, encouraging the development of multipurpose miRNA signatures as diagnostic or prognostic tools (46)(47)(48). For instance, combination of miR-15a-5p, miR-16, miR-24-3p, miR-28-5p, miR-34a, miR-96, miR-182, and miR-224, which have been proposed as molecular biomarkers with significant prognostic value in colorectal cancer (CRC); has already been proposed as a prognostic signature in this malignancy (49)(50)(51)(52)(53)(54)(55)(56)(57); another very important miRNA that could be added in this molecular signature is miR-21, a predictor of metastatic tumor potential in this cancer (58). Similar signatures consisting of miRNAs have been proposed in prostate cancer (59,60), laryngeal squamous cell carcinoma (61), and other human malignancies (62).…”
Section: Introductionmentioning
confidence: 99%
“…Among the evaluated studies, 49 demonstrated the downregulation of miR-199b 47, 48 , miR-6852 106 , miR-302c 67 , miR-466 68 , miR-650 123 , miR-196b-5p 70 , miR-944 71 , miR-30d 72 , miR-296 73 , miR-187 124 , let-7a-5p 98 , miR-132 99 , miR-206 100 , miR-148a 125 , miR-33b 76 , miR-99b-5p 120 , miR-154 78 , miR-217 126 , miR-149 79 , miR-194 80 , miR-7 56 , miR-24-3p 54 , miR-29b 127 , miR-15a 34 , miR-16 34, 36 , miR-204-5p 128 , miR-96-5p 121 , miR-193a-5p 108 , miR-100 81 , miR-133a 41 , miR-139-5p 129 , miR-124-5p 130 , miR-335 82 , miR-378 101 , miR-126 40 , miR-378a-3p 58 , miR-378a-5p 58 , miR-218 83 , miR-138 110 , miR-625 111 , miR-212 112 , miR-124 131 , miR-22 49 , miR-133b 39 , miR-193a-3p 104 , miR-195 113 and miR-30c 103 associated with worse prognosis (lower overall survival) of CRC patients. Fifty-six studies identified the upregulation of miR-181a 3133 , miR-182 43, 44 , miR-1296 84 , miR-888 64 , miR-28-5p 132 , miR-183 45, 46 , miR-200c 114 , miR-34a 133 , miR-15a-5p 134 , miR-181c 135 , miR-24-3p 53 , miR-16 35 , miR-7 55 , miR-96 86 , miR-1260b 115 , miR-20a-5p 63 , miR-517a 87 , miR-503 136 , miR-106b 88 , miR-211 137 , miR-320e 89 , miR-592 90 , miR-196a 57 , miR-196b 57 , miR-376a …”
Section: Resultsmentioning
confidence: 99%
“…In total, 17 studies demonstrated the downregulation of 18 miRs associated with worse disease free-survival such as miR-196b-5p 70 , miR-944 71 , miR-30d 72 , miR-22 50 , miR-296 73 , miR-199b 47 , miR-187 124 , let-7a-5p 98 , miR-132 99 , miR-29b 127 , miR-15a 34 , miR-16 34 , miR-34a-5p 65 , miR-193a-5p 108 , miR-138 110 , miR-126 8 , miR-212 112 and miR-124 131 . Twenty-one studies associated the upregulation of miR-888 64 , miR-28-5p 132 , miR-183 45 , miR-200c 114 , miR-34a 133 , miR-15a-5p 134 , miR-181c 135 , miR-24-3p 53 , miR-16 35 , miR-96 86 , miR-1260b 115 , miR-20a-5p 63 , miR-517a 87 , miR-503 136 , miR-106b 88 , miR-320e 89 , miR-196a 57 , miR-196b 57 , miR-224 51 , miR-494 61 , miR-181a 32 , miR-21 25, 26, 30 and miR-155 30 with worse disease free-survival.…”
Section: Resultsmentioning
confidence: 99%
“…miR-28 was shown to regulate T-cell exhaustion via controlling the expression of inhibitory receptors such as PD-1 and T-cell immunoglobulin domain and mucin domain 3. Furthermore, the upregulation of miR-28-5p was linked to poor overall survival and shorter disease-free periods in patients with CRC, independent from the clinicopathological features of the tumor or the therapeutic protocol [60]. Furthermore, the upregulation of miR-28-5p was linked to poor overall survival and shorter disease-free periods in patients with CRC, independent from the clinicopathological features of the tumor or the therapeutic protocol [60].…”
Section: Mirnas Regulation Of Pd-1 Checkpoint Proteinmentioning
confidence: 94%
“…The inhibition of miR-28 led to the upregulated expression of such inhibitory receptors [59]. Furthermore, the upregulation of miR-28-5p was linked to poor overall survival and shorter disease-free periods in patients with CRC, independent from the clinicopathological features of the tumor or the therapeutic protocol [60]. Wei et al [61] have indicated that miR-138 targets the 3 0 UTRs of PD-1 and CTLA-4, inhibiting their expression.…”
Section: Mirnas Regulation Of Pd-1 Checkpoint Proteinmentioning
confidence: 99%